2011
DOI: 10.3109/0886022x.2011.623440
|View full text |Cite
|
Sign up to set email alerts
|

Troponins in Acute Kidney Injury

Abstract: Aim: To investigate and describe cardiac troponins in subjects with acute kidney injury (AKI). Methods: A prospective observational study of troponin in subjects presenting with AKI in a tertiary hospital. Creatine kinase-MB (CKMB), troponin I (Abbott Laboratories), and troponin T (Roche 4th generation) were measured. Patients with conditions known to cause elevated troponin levels were excluded. Results: Nineteen subjects were enrolled in the study. Six subjects had troponin I and T concentrations above the 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…ET-1 also upregulates NT-proBNP, which is associated with hypotension, hyponatremia and venous congestion [45, 46], variables associated with the hemodynamic explanation of CRS-1. TnI was also found associated to the worsening of renal function in ACS; previous studies demonstrated that AKI alone can raise the levels of TnI indicating that AKI can also lead to a cardiac injury and that these effects seem to be bidirectional [47]. …”
Section: Discussionmentioning
confidence: 99%
“…ET-1 also upregulates NT-proBNP, which is associated with hypotension, hyponatremia and venous congestion [45, 46], variables associated with the hemodynamic explanation of CRS-1. TnI was also found associated to the worsening of renal function in ACS; previous studies demonstrated that AKI alone can raise the levels of TnI indicating that AKI can also lead to a cardiac injury and that these effects seem to be bidirectional [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Other disease processes in the study population may have influenced the measured cTnI concentration. Human patients with renal insufficiency can have measurable cTnI concentrations, even in the absence of clinically suspected ischemia . Cardiac troponin I has been correlated with renal function in patients with chronic kidney disease .…”
Section: Discussionmentioning
confidence: 99%
“…Human patients with renal insufficiency can have measurable cTnI concentrations, even in the absence of clinically suspected ischemia. 53 Cardiac troponin I has been correlated with renal function in patients with chronic kidney disease. 54 The cause of increased cTnI concentration in renal disease is assumed to be multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjustment for confounders, preprocedural MA was still independently associated with a higher incidence of PMN in subjects with eGFR ≥60 ml/min, without MA, and undergoing (Table 4). Similarly, Song et al (2012) found that 32% of subjects (6/19) had troponin I and T concentrations above the 99th percentile of a reference population, without known confounders, resulting in elevated troponin levels. This suggests that impaired renal function disease influences plasma cardiac troponin levels in AKI as well as in chronic kidney failure.…”
Section: Discussionmentioning
confidence: 99%